Classification Of Abnormal Cervical Cells Using Hierarchical Multilayered Perceptron Network. - Mat Isa, Nor Ashidi; Mashor, Mohd Yusoff; Othman, Nor Hayati (2003)

(untitled)
The paper discusses the use of neural network to classify the types of cervical cells based on Bethesda system; which are normal, low-grade squamous intraepithelial lesion (LSIL) and high-grade squamous intraepithelial lesion (HSIL). The current study proposed new neural network architecture, namely hierarchical multilayered perceptron (HiMLP) network.